Affective Instability and Emotion Dysregulation as a Social Impairment - Schmidt, Philipp (Frontiers in Psychology, 2022)
Borderline personality disorder is a complex psychopathological phenomenon. It is usually considered to consist in a vast instability of different aspects that are central to our experience of the world, manifest as “a pervasive pattern of instability of interpersonal relationships, self-image, and affects, and marked impulsivity” (American Psychiatric Association, 2013, p. 663). Typically, of the instability triad – in (1) self, (2) affect and emotion, and (3) interpersonal relationships – only the first two are described, examined, and conceptualized from an experiential point of view. In this vein, disorders of self have often motivated analyses of self-experience and the sense of self, affective disorders have been frequently considered in the light of emotional experience and its phenomenological structure. Alterations in the phenomenology of social experience have found comparatively little traction when it comes to the conceptualization of the interpersonal disturbances in borderline. In this paper, I argue that interpersonal instability in borderline consists in much more than fragile and shifting relationships but also involves peculiar styles in experiencing others. These styles likely explain great part of the borderline typical patterns of interpersonal turmoil and so deserve more attention. To better understand these styles, I explore the phenomenological structure of borderline affective instability and describe the implications it might have for how a person experiences and relates to other people. Considering core aspects of borderline affective instability, such as alexithymia, emotional contagion, emotion dysregulation, and chronic emptiness, I propose borderline can be interpreted as a disturbance of interaffective exchange, which gives rise to a peculiar way of experiencing others and amounts to a social impairment.